The Flash Magazine - 2017 edition - University of Embu (University of Embu, 2017)
The second issue of The Flashlight Magazine highlights the key events that happened at the University of Embu in the second semester of the academic year 2016/2017. The semester has seen a lot of developments in different areas. This issue of the magazine features key events at the University from the time it was awarded Charter becoming a fully-fledged Public University and all the news and key highlights that happened at the University from January 2017 to April 2017. The highlights are featured and captured by different sections of the University and key personnel mandated with the responsibility of Publicity and Marketing of the University. games, cartoons and different genres of animation. Members of staff are also encouraged to contribute creative and informative works. The editors have spared a section for culture and entertainment but can only publish creative and quality works. Apart from setting the pace as the ambassador of the UoEm, The Flashlight magazine is the main forum for highlighting various activities at the University. Some of the highlights are on academics, research and extension, planning and development initiatives, corporate social responsibility, students’ affairs, and linkages. EDITORS Dr. Michael Oyoo Weche Dr. Cyrus Ngumo MEMBERS The Editorial Board welcomes constructive contribution from all stakeholders to make the subsequent issues better. We wish to invite our partners from different sections and areas to support the Magazine in terms of making it a platform for advertising, sharing information and research. The Magazine is published on semester basis and made accessible to all stakeholders through the print and online version.